Evaluation of the influence of offshore wind farm noise on the fishes and dolphins in the Pearl River Estuary - Zhongchang Song; Weijie Fu; Hongquan Li; Yingnan Su; Zhanyuan Gao; Wenxin Fan; Jiangang Hui; Wenzhan Ou; Shengyao Sun; Teng Wang; Honghui Huang; Yu Zhang (Water Biology and Security)
In this study, we recorded the noise radiating from a wind farm and evaluated its potential impact on the fishes and Indo-Pacific humpback dolphins (Sousa chinensis) residing in the Pearl River Estuary. The pile driving pulses, recorded 30 ​m from the construction site, had a mean zero-to-peak sound pressure level of 195.1 ​dB (re 1 ​μPa) (n ​= ​238), exceeding the hearing thresholds of both fishes and Indo-Pacific humpback dolphins. The operational noise from the wind farm was significantly lower in amplitude; therefore, our analysis primarily focused on the radiation of pile driving noise. Acoustic measurements taken at three different distances during pile driving events supported the development of an acoustic propagation model, which was then used to predict the sound exposure levels of pile driving pulses radiating from 5 ​m below the water surface. By referring to established noise exposure metrics, we estimated an impact zone of 12.8 ​m for fishes. For the Indo-Pacific humpback dolphins, the permanent and temporary threshold shift zones were predicted to be 32.4 ​m and 580.9 ​m, respectively. Our findings underscore the importance of increasing our understanding on hearing sensitivities of the local inhabitants in the Pearl River Estuary and identify their core habitats. This approach enabled us to use the model to estimate impact zones and better protect the local marine life from the effects of pile driving noise radiation.